Romanticism as a pseudo-literary and pseudo-historical label used in discussions and literary polemics in interwar Czechoslovakia - Gwóźdź-Szewczenko, Ilona (Poznańskie Studia Slawistyczne, 2011)
The article deals with the specific presence of the term romanticism in the interwar period (1918–1939) in Czechoslovakia. In the introduction, the author stresses the lack of a precise definition of the term as well as two ways of understanding it. On the one hand, the term romanticism refers to the complex historical and literary movement that originated in the second half of the 18th century. On the other hand, however, it is associated with something trivial, which does not deserve much attention. The author attempts to analyse the way  the  term  is  used  in  literary  discussions  and  polemics  in  the  interwar period in Czechoslovakia. The author comes to the conclusion that the term 'romanticism' was a sort of historical and literary label stuck to adversaries in order to belittle them and their ideas.